2023
DOI: 10.1021/acs.analchem.2c03156
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Point-of-Care Electrodes for Ultrasensitive Detection of Bladder Tumor-Relevant miRNA in Urine

Abstract: Portable point-of-care testing (POCT) is currently drawing enormous attention owing to its great potential for disease diagnosis and personal health management. Electrochemical biosensors, with the intrinsic advantages of cost-effectiveness, fast response, ease of miniaturization, and integration, are considered as one of the most promising candidates for POCT application. However, the clinical application of electrochemical biosensors-based POCT is hindered by the decreased detection sensitivity due to the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…[43] Chen et al achieved POCT diagnosis of Bladder Tumor-Relevant miRNA-21 by a flexible electrochemical device. [44] However, miRNAs have the characteristics of short sequence and strong similarity. It is urgent to develop specific and highspeed detection methods.…”
Section: Mirnasmentioning
confidence: 99%
“…[43] Chen et al achieved POCT diagnosis of Bladder Tumor-Relevant miRNA-21 by a flexible electrochemical device. [44] However, miRNAs have the characteristics of short sequence and strong similarity. It is urgent to develop specific and highspeed detection methods.…”
Section: Mirnasmentioning
confidence: 99%
“…Our laboratory has used the ferri/ferrocyanide redox system to provide electrochemical readouts and generated robust data from reusable glassy carbon electrodes (limit of detection of 20 fM) [46], and disposable screenprinted electrodes (17 fM) [47], successfully recapitulating urinary miRNA RT-qPCR data from people with DKD [46,47]. Chen et al [48] produced flexible single-walled carbon nanotube electrodes to which they bound DNA complementary to miR-21, a biomarker of bladder cancer. They then hybridised the sensor with target miR-21 before addition of exogenous methylene blue reporter.…”
Section: Electrochemical Mirna Biosensorsmentioning
confidence: 99%
“…They then hybridised the sensor with target miR-21 before addition of exogenous methylene blue reporter. These workers achieved a limit of detection of 3 fM, and monitored urinary miR-21 to successfully distinguish between prostate and bladder cancer patients compared with controls [48].…”
Section: Electrochemical Mirna Biosensorsmentioning
confidence: 99%
“…16,17 For example, Chen et al reported an integrated flexible electrode for the rapid detection of cancer-related RNA in human urine samples with excellent sensitivity and stability. 18…”
Section: Introductionmentioning
confidence: 99%